Analisis Faktor-Faktor yang Mempengaruhi Implementasi Kebijakan Vaksinasi Covid-19 Pada Dinas Kesehatan Kabupaten Kepulauan Mentawai - Zebua, Arifman; Putera, Roni Ekha; Karnedi, Karnedi (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2023)
This study, which aims to analyze the factors that influence the implementation of the Covid-19 vaccination policy at the Mentawai Islands District Health Office, is motivated by the unequal implementation of the Covid-19 vaccination policy for the community, especially at the Mentawai Islands District Health Office. This type of research uses a quantitative approach with multiple linear regression method. Data collection techniques with questionnaires. The respondents of this study were 95 employees at the Mentawai Islands District Health Office. The sampling method used the total sampling method where the entire population in this study was used as the research sample. Hypothesis testing is calculated with the IBM Statistical Package for Social Science (SPSS) version 24.0 program. The results of this study it was found that partially and simultaneously communication, resources, disposition, and bureaucratic structure had a positive and significant effect on the implementation of the Covid-19 vaccination policy at the Mentawai Islands District Health Office.